Design of Vertical Village in Pantai Burung Village Medan City (Ecology Architecture) - Wahyuni Zahrah; Muhammad Hadi Syah Putra (Talenta Publisher, 2018)
Illegal settlement becomes one of the factors that cause the order of an irregular city and tend to slum. Its location in the region of the River could potentially interfere with the conservation of the river. One of the ways t design and organize the settlement as well city to make it better. This design aims to rehabilitate the area from physical, environment, facilities and infras community. In this case, a vertical research because of the narrowest area and the progressing human’s life every year. With this design, land use can be optimally, and the collaboration of architecture ecology approach which exploits the facility naturally that will be exposed human’s need with should not have to spend expenditure too much. Residential unit use container materials to provide a flexible dwelling, easy to put on and work quickly. Then, to reduce the effect of radiation is acquired by container material that contained a metal using isolation and giving aperture maximally to create a thermal situation comfortably for people. The a watering conservation is programmed by apply biofilter to distill the gray improving the economy, it will on organized by utilizing area gardening on floodplain a river that can be a part of the communal area as the waterfront.